Symposium 9: Team and Community Building of Students of Business Informatics: Influence Factors in Blended Environments - Figl, Kathrin; Motschnig-Pitrik, Renate; Derntl, Michael (Proceedings of the International Conference on Networked Learning, 2006)
For students as well as professionals in business informatics the ability to work in teams and to be part of a supporting network are major success factors. This observation appears to be just one instance of a more general goal, namely the fostering of meta-cognitive skills and attitudes in new curricula. In our research and educational practice we aim to contribute to this goal by investigating and implementing the key factors that allow students to become more capable of working in teams. In this paper we report on our initial investigations, the methods used, and observations made on teamwork in settings that blend face-to-face and online elements. The results confirm that positive personal relationships, attitudes and context-related factors in a motivating atmosphere appear to be pivotal to good team and group effort. A situated use of transparent, usable online elements has the potential to make cooperation and communication broader and more effective.